Randić spectrum of the weakly zero-divisor graph of the ring ℤn - Nadeem Ur Rehman; Nazim; Ahmad M. Alghamdi; Eman S. Almotairi (AKCE International Journal of Graphs and Combinatorics)
In this article, we find the Randić spectrum of the weakly zero-divisor graph of a finite commutative ring [Formula: see text] with identity [Formula: see text], denoted as [Formula: see text], where [Formula: see text] is taken as the ring of integers modulo [Formula: see text]. The weakly zero-divisor graph of the ring [Formula: see text] is a simple undirected graph with vertices representing non-zero zero-divisors in [Formula: see text]. Two vertices, denoted as a and b, are connected if there are elements x in the annihilator of a and y in the annihilator of b such that their product xy equals zero. In particular, we examine the Randić spectrum of [Formula: see text] for specific values of [Formula: see text], which are products of prime numbers and their powers.